1985
DOI: 10.1177/002203458506400406
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Pulpal Cells and Inductive Influences of Various Matrices with Reference to Pulpal Wound Healing

Abstract: Based on recent literature, the dynamics of mesenchymal cells in transplantation of various tissues and matrices, as well as the origin of new odontoblasts which participate in the formation of the dentin bridge, are described. Experiments involving implantation of pulp, periosteum, perichondrium, treated dentin, and bone matrices were performed to emphasize the capability of these cells to produce hard tissue. Light and electron microscopic and autoradiographic studies were carried out to clarify the origin o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
131
0
10

Year Published

1990
1990
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 233 publications
(150 citation statements)
references
References 50 publications
9
131
0
10
Order By: Relevance
“…Indeed, fibroblast-like cells are able to differentiate into either osteoblasts or chondroblasts depending on the nature of the surrounding matrix and the amounts of vascular-derived oxygen (Indue et al, 1981). Given the proper environment, they may also be able to differentiate into replacement odontoblasts, as suggested by Fitzgerald (1979), Yamamura et al (1980, Yamamura (1985) and Tziafas and Kolokuris (1990). The shift in numbers of fibroblast-like and odontoblast-like cells in zone 1 between Days 8 and 10, was not seen between Days 10 and 12 in zone 1.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Indeed, fibroblast-like cells are able to differentiate into either osteoblasts or chondroblasts depending on the nature of the surrounding matrix and the amounts of vascular-derived oxygen (Indue et al, 1981). Given the proper environment, they may also be able to differentiate into replacement odontoblasts, as suggested by Fitzgerald (1979), Yamamura et al (1980, Yamamura (1985) and Tziafas and Kolokuris (1990). The shift in numbers of fibroblast-like and odontoblast-like cells in zone 1 between Days 8 and 10, was not seen between Days 10 and 12 in zone 1.…”
Section: Discussionmentioning
confidence: 91%
“…These patterns suggest a migration of cells from the deeper pulp (represented by zone 3) through an intermediate area (zone 2) into the area directly against the capping agent (zone l), and support the findings of Sveen and Hawes (1968), Feit et al (1970), Yamamura er al. (1980) and Yamamura (1985). Tziafas and Kolokuris (1990) demonstrated that cells in the deep pulp can differentiate into odontoblasts when exposed to demineralized dentine surgically implanted in the pulp.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations